2020
DOI: 10.1016/j.invent.2020.100357
|View full text |Cite
|
Sign up to set email alerts
|

A pragmatic factorial randomized controlled trial of transdiagnostic internet-delivered cognitive behavioural therapy: Exploring benefits of homework reflection questionnaires and twice-weekly therapist support

Abstract: With the growing demand for internet-delivered cognitive behavioural therapy (iCBT), this pragmatic factorial (2 × 2 × 2) randomized controlled trial evaluated strategies for facilitating iCBT engagement and outcomes in routine care. Specifically, the benefits to patients and therapists of using homework reflection questionnaires and offering patients twice-weekly therapist support were examined. Patients ( n = 632) accepted into iCBT for depression and/or anxiety were randomly assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 51 publications
(46 reference statements)
2
36
0
Order By: Relevance
“…Descriptively, these outcomes are comparable to the most recent published outcomes of the Wellbeing Course offered by the Online Therapy Unit to the general population of Saskatchewan [ 63 ]. Effect sizes, percentage changes, and reliable change rates were comparable for all available symptom measures with the possible exception of the SIAS-6/SPS-6, which appeared to show better outcomes for the Wellbeing Course.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Descriptively, these outcomes are comparable to the most recent published outcomes of the Wellbeing Course offered by the Online Therapy Unit to the general population of Saskatchewan [ 63 ]. Effect sizes, percentage changes, and reliable change rates were comparable for all available symptom measures with the possible exception of the SIAS-6/SPS-6, which appeared to show better outcomes for the Wellbeing Course.…”
Section: Discussionsupporting
confidence: 71%
“…Effect sizes, percentage changes, and reliable change rates were comparable for all available symptom measures with the possible exception of the SIAS-6/SPS-6, which appeared to show better outcomes for the Wellbeing Course. However, mean pretreatment social anxiety symptoms were considerably less severe in the present sample than in the Online Therapy Unit’s clients [ 63 ], and the smaller change in symptoms found in this study may be due, in part, to a floor effect. Of note, the present findings show that the PSP Wellbeing Course was moderately effective for treating anger, which has not been measured in research on the Wellbeing Course.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Therapists contact clients on a designated day once-weekly for 8 weeks, although in some trials the amount of contact has varied (e.g., optional, twice-weekly). 17 20 Most contact includes asynchronous secure emails, with therapists spending 15 to 20 minutes composing messages after reviewing patient iCBT progress, symptom measures, and messages. Therapists also phone patients when there is a large symptom increase, messages suggest suicide risk, patients have not logged in for a week, and or a phone call would more easily address patient concerns.…”
Section: Methodsmentioning
confidence: 99%
“…Past research on the Wellbeing Course has shown outcomes are strong whether delivered by therapists who specialise in iCBT or by therapists who primarily deliver face-to-face treatment. 15 , 16 Furthermore, outcomes are comparable with varying support (i.e., once-weekly support compares to optional support, 17 , 18 twice-weekly support, 19 and one-business-day support 20 ). Still, other trials have studied therapist behaviours in iCBT 21 23 and outcomes of iCBT for alcohol misuse, 24 for various chronic health conditions, 25 30 and for specific populations like postpartum depression/anxiety 31 or university students.…”
Section: Introductionmentioning
confidence: 96%